The Cord Blood Apgar: a novel scoring system to optimize selection of banked cord blood grafts for transplantation - Page, Kristin M. (2011)
BACKGROUND: Engraftment failure and delays, likely due to diminished cord blood unit (CBU) potency, remain major barriers to the overall success of unrelated umbilical cord blood transplantation (UCBT). To address this problem, we developed and retrospectively validated a novel scoring system, the Cord Blood Apgar (CBA), which is predictive of engraftment after UCBT. STUDY DESIGN AND METHODS: In a single-center retrospective study, utilizing a database of 435 consecutive single cord myeloablative UCBTs performed between January 1, 2000, to December 31, 2008, precryopreservation and postthaw graft variables (total nucleated cell, CD34+, colony-forming units, mononuclear cell content, and volume) were initially correlated with neutrophil engraftment. Subsequently, based on the magnitude of hazard ratios (HRs) in univariate analysis, a weighted scoring system to predict CBU potency was developed using a randomly selected training data set and internally validated on the remaining data set. RESULTS: The CBA assigns transplanted CBUs three scores: a precryopreservation score (PCS), a postthaw score (PTS), and a composite score (CS), which incorporates the PCS and PTS values. CBA-PCS scores, which could be used for initial unit selection, were predictive of neutrophil (CBA-PCS ≥ 7.75 vs. <7.75, HR 3.5; p < 0.0001) engraftment. Likewise, CBA-PTS and CS scores were strongly predictive of Day 42 neutrophil engraftment (CBA-PTS ≥ 9.5 vs. <9.5, HR 3.16, p < 0.0001; CBA-CS ≥ 17.75 vs. <17.75, HR 4.01, p < 0.0001). CONCLUSION: The CBA is strongly predictive of engraftment after UCBT and shows promise for optimizing screening of CBU donors for transplantation. In the future, a segment could be assayed for the PTS score providing data to apply the CS for final CBU selection.